Protective effect of resveratrol against toxicity induced by the mycotoxin, zearalenone in a rat model. (December 2020) - Virk, Promy; Al-mukhaizeem, Nourah Abdual Rahman; Bin Morebah, Sara Hamad; Fouad, Dalia; Elobeid, Mai
Abstract: Contamination of cereal crops with zearalenone (ZEA), a mycotoxin produced by Fusarium fungi, is a worldwide health concern. The study assessed the ameliorative potential of resveratrol (RSV), a potent antioxidant against ZEA induced toxicity in adult male Wistar rats. Rats (n = 40), with an average weight of 100–150 g were used for the exposure study for three weeks. The animals were divided into four groups (I to IV) each comprising 10 rats. Group I was kept as negative control and was administered normal saline. Group II and III were exposed to 2 mg/kg of the mycotoxin, ZEA administered intraperitoneally once every week. Group III was treated with resveratrol (RSV) orally (5 mg/kg) daily. Group IV was treated only with resveratrol (5 mg/kg/daily) as a positive control. The protective effect of resveratrol was evaluated on; biochemical variables, biomarkers of oxidative stress, markers of immunotoxicity, and DNA damage. The findings showed that exposure to ZEA elicited oxidative stress and modulated the antioxidant enzyme activities. A disarray in the lipid profile, parameters of the humoral and cellular immune response; serum cytokines and immunoglobulins was also observed. Further, COMET assay showed detectable DNA lesions. Taken together, RSV was efficacious in reducing and/or reversing the ZEA induced toxicity. Graphical abstract: Image 1 Highlights: The study highlights the manifestation of the zearlenone induced mycotoxicosis in terms of oxidative damage, hepatotoxicity, immunotoxicity and DNA damage. Based on a broad assessment of the parameters evaluated, the key findings clearly suggest an ameliorative effect of resveratrol against the zearalenone-induced immunotoxicity and genotoxicity as the treatment significantly reversed the alterations caused. This could be attributed to its potent antioxidant status. Taken together our findings unravelled the use of resveratrol as a possible mitigator in zearlenone-induced toxicity in rats.